Effects of carbonized process on quality control, chemical composition and pharmacology of Typhae Pollen: A review. (24th April 2021) - Gao, Mingliang; Lan, Jinshan; Bao, Beihua; Yao, Weifeng; Cao, Yudan; Shan, Mingqiu; Cheng, Fangfang; Chen, Peidong; Zhang, Li
Abstract: Ethnopharmacological relevance: Carbonized Typhae Pollen (CTP), a processed product of Typhae Pollen after stir-fried, is a well-known Traditional Chinese Medicine (TCM) with functions of removing blood stasis and hemostasis. Aim of review: The aim of this study is to summarize and discuss up-to-date information on quality control of CTP, and effects of carbonized process on phytochemistry and biological activities. We hope this review could provide feasible insights for further studies of CTP on its material basis and pharmacological effect mechanism. Material and methods: The information of TP before and after carbonized process was collected from online databases ( PubMed, CNKI, Google Scholar, Baidu Xueshu, Web of Science, SpringerLink, Wiley Online Library, SciFinder and Chemical book). Meanwhile local books, published and unpublished Ph.D., MSc. dissertations were also taken into consideration. Results: A total of 27 Ph.D., MSc. dissertations and 208 articles were collected from online database, from which 122 compounds of TP were collected, but only two researches focused on the chemical compositions of CTP. Introductions of new technologies and intelligent processing equipment developments are considered as two main solutions to the quality control of CTP. CTP is a well-known ethnic medicine in China with a fantastic efficacy in curing bleeding caused by blood stasis. Flavonoids were reported as the main active compounds for removing blood stasis while the enhanced hemostatic activity were consistent with flavonoid aglycones. Modern pharmacological researches showed that CTP has wound healing activity, effects on blood vessels, antithrombotic activity, hemostatic activity, antioxidant activity and immunomodulatory activity. Conclusions: Although CTP has been widely used in clinic, there are some problems blocking its further development. Unknown mechanism and uncertain active compounds might be the main reasons for few rules on controlling the quality of CTP. It is necessary to investigate the mechanisms and the relationship between carbonized process and the changes in constituents as well as pharmacological effects. This is essential to promote the safe clinical use of CTP. Graphical abstract: Image 1